"Der Noth gehorchend, nicht dem eignen Trieb" - Nascent Necessity and Opportunity Entrepreneurs in Germany: Evidence from the Regional Entrepreneurship Monitor (REM) - Joachim Wagner (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2005)
Using a large recent representative sample of the adult German population this paper demonstrates that nascent necessity and nascent opportunity entrepreneurs are different with respect to some of the characteristics and attitudes considered to be important for becoming a nascent entrepreneur, and that they behave differently. Given the lack of longitudinal data, however, we have no information about the performance of entrepreneurs from both groups in the longer run.
Keywords: J23; 330; Necessity entrepreneurship; opportunity entrepreneurship; Germany; REM; Unternehmer; Unternehmensgründung; Region; Deutschland